Oral impacts on daily performance: Validity, reliability and prevalence estimates among Indian adolescents. Issue 2 (3rd May 2017) - Nagarajappa, R; Batra, M; Sanadhya, S; Daryani, H; Ramesh, G
Abstract: Background: Dental diseases negatively influence people's oral health‐related quality of life and thus their perceived need for dental care. Objectives: To test the validity and reliability of an Indian version of Oral Impacts on Daily Performance (OIDP) index for college students and to identify age and sex‐specific OIDP prevalence estimates. Methods: Cross‐sectional descriptive survey was conducted among 800 professional and non‐professional bachelor degree college students of Udaipur, India aged between 17 and 24 years. Oral health‐related quality of life among the college students was assessed through OIDP, tested for validity and reliability and then prevalence rates were estimated. Chi square test was employed for statistical analysis. Cronbach's alpha was found to be 0.82. Results: Sixty percent subjects reported at least one oral impact in last 6 months with overall mean OIDP score of 2.49±3.92. The most commonly affected performances were cleaning teeth (24%) and eating (12%). A significant association in oral impacts on daily performances among college students was observed with age ( P =.001) but not with gender ( P =.053). Conclusions: The validity and reliability of OIDP and also the prevalence of oral health‐related impacts were found to be high. OIDP index showed acceptable psychometric properties in the context of an oral health survey among Indian college students.